2018
DOI: 10.3390/w10101312
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Contour Farming and Filter Strips on Ecosystem Services

Abstract: The failing ecosystem services in Thika-Chania catchment is manifested in the deterioration of water quality, sedimentation of reservoirs, and subsequent increase in water treatment costs due to high turbidity. The services can be restored by implementing relevant soil and water conservation practices to enhance flow regulation and control sediment yield. The impacts of contour farming and filter strips on water and sediment yield were evaluated using Soil Water and Assessment Tool (SWAT), Texas A&M Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The study by Mosbahi and Benabdallah [54] reported that SWAT model was capable of identifying the optimal management practice under a specific land use in a Tunisian semi-arid catchment. The SWAT model was used to evaluate the effectiveness of contour farming and filter strips on ecosystem services in the Thika-Chania catchment, Kenya [55]. Similarly, Gharibdousti et al [45] showed that SWAT model can be used to prioritize feasible BMPs on fields in agriculture-pasture intensive watersheds, Southwestern Oklahoma, USA.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Mosbahi and Benabdallah [54] reported that SWAT model was capable of identifying the optimal management practice under a specific land use in a Tunisian semi-arid catchment. The SWAT model was used to evaluate the effectiveness of contour farming and filter strips on ecosystem services in the Thika-Chania catchment, Kenya [55]. Similarly, Gharibdousti et al [45] showed that SWAT model can be used to prioritize feasible BMPs on fields in agriculture-pasture intensive watersheds, Southwestern Oklahoma, USA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Ayele et al [25] in the Upper Blue Nile Basin. Gathagu et al [52] used the SWAT model in the Thika-Chania catchment in Kenya to evaluate soil and conservation practices to control sediment yield, and found satisfactory results. Licciardello et al [53] also evaluated the SWAT model in simulating sediment deposition in a Sicilian reservoir by comparing with different bathymetric measurements.…”
Section: Assessment Of Swat Model Performance Efficiencymentioning
confidence: 99%
“…Soil erosion not only causes the loss of water and soil resources and the destruction of land productivity, but also the harm to human survival 47–49 . Due to soil erosion, ecological problems such as soil fertility decline have exacerbated the fragility of ecosystems and will affect human production and life (Fig.…”
Section: Methodsmentioning
confidence: 99%